Role of digital health monitoring in the management of diabetic patients with hypertension - PA, Balaji; Varne, Smitha R (Indian Journal of Integrative Medicine, 2024)
As we have entered a digital era, which is exponentially growing, there is definitive need for the health sector to embrace and utilize the benefits of information and technology for better control of highly prevalent chronic health disorders like diabetes mellitus and hypertension. Despite few challenges and limitations, numerous research studies and data have demonstrated that the digital health monitoring can result in better control of hypertension and diabetes and prevent complications in large number of high-risk patients.